Institutional climate and evaluation of educational quality. Educational institution No. 6048 Jorge Basadre, Lima. - Caballero Quispe , Beatriz Jane (2025)
One of the trends in public educational institutions is to establish the relationship between institutional climate and educational quality, and this is the objective of this study. A quantitative approach using a hypothetical deductive method, ordinal design, correlational descriptive design, and cross-sectional analysis allows us to obtain the results through descriptive and inferential statistical analysis using SPSS version 25. We used a sample of 24 teachers, and data collection was conducted using a survey technique and a Likert-scale questionnaire for comparison. The results show that the relationship is accepted, as the sigma of significance is .000 and the correlation coefficient is .916 for the general hypothesis.